2022
DOI: 10.1186/s12870-021-03371-1
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of the Liriodendron chinense WRKY gene family and its diverse roles in response to multiple abiotic stress

Abstract: Background Liriodendron chinense (Lchi) is a tree species within the Magnoliaceae family and is considered a basal angiosperm. The too low or high temperature or soil drought will restrict its growth as the adverse environmental conditions, thus improving L. chinense abiotic tolerance was the key issues to study. WRKYs are a major family of plant transcription factors known to often be involved in biotic and abiotic stress responses. So far, it is still largely unknown if and how the LchiWRKY g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 148 publications
2
36
0
Order By: Relevance
“…Transcription factors (TFs) are important proteins, which bind to specific DNA motifs, regulate gene expression and play an important role in plant stress response ( Wu et al, 2022 ). The present study found that 121 tomato UGT genes interacted with 12 different transcription factors, 90% of which were regulated by glutathione under CHT stress.…”
Section: Discussionmentioning
confidence: 99%
“…Transcription factors (TFs) are important proteins, which bind to specific DNA motifs, regulate gene expression and play an important role in plant stress response ( Wu et al, 2022 ). The present study found that 121 tomato UGT genes interacted with 12 different transcription factors, 90% of which were regulated by glutathione under CHT stress.…”
Section: Discussionmentioning
confidence: 99%
“…RNA integrity was assessed using the RNA Nano 6000 Assay Kit of the Bioanalyzer 2100 system (Agilent Technologies, CA, USA). The library preparations were sequenced on an Illumina Novaseq 6000 platform, and 150 bp paired-end reads were generated [ 89 ]. Three replicates were set for each independent experiment.…”
Section: Methodsmentioning
confidence: 99%
“…According to previous studies, AAAPs were involved in the low temperature, heat temperature, drought stress treatments in many plants [35,54,55]. In this study, we analyze the LcAAAP gene expression pattern based on the stress transcriptome data of hybrid Liriodendron [56,57]. A total of 13 genes in hybrid Liriodendron leaves were able to respond to the three abiotic stress treatments.…”
Section: Discussionmentioning
confidence: 99%
“…How plants adapt to external abiotic stresses involves a very complex gene regulatory network, and a variety of transcription factors are usually involved in this process [58][59][60]. In previous studies, we found that WRKY and MYB genes were involved in regulating the response of hybrid Liriodendron to stress [56,57]. Therefore, we constructed the co-expression network based on the LcAAAP, LcMYB, and LcWRKY genes to explore the interactions between them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation